Immune dissociation during acute hepatitis E infection. (October 2019) - Debes, Jose D.; Groothuismink, Zwier M.A.; Doukas, Michail; de Man, Robert A.; Boonstra, Andre
Highlights: Description of autochthonous cholestatic hepatitis E in Europe. Bimodal development of acute hepatitis with negative virus in blood. Found dissociation of peripheral immune responses during intrahepatic hepatitis E virus replication following negativization in blood. Abstract: Objective: We report the immune response during a case of acute HEV response in a patient with an acute hepatitis E virus (HEV) genotype 3 infection in the Netherlands. Methods: Cytokine evaluation was performed via multiplex cytokine array for 65 immune markers in plasma during the different phases of hepatitis. Results: The patient initially presented with features typical of acute viral hepatitis, with detectable HEV RNA in blood. This evolved into a cholestatic disease following peripheral clearance of the virus, leading to the demise of the patient. Real time PCR revealed the presence of HEV in liver tissue, suggestive of active intrahepatic infection despite clearance in blood. During the phase of detectable HEV RNA in serum, there was a surge in T-cell-related immune mediators, as well as interferon alpha and interferon gamma-induced protein 10 (IP-10), characteristic of a viral infection. After clearance of the virus in the blood and development of cholestatic hepatitis, several inflammatory markers subsided, followed by an increase in immune factors related to anti-inflammatory activity, as well as monocyte/macrophage-related markers, likely due to the intrahepatic presence of the virus. Conclusions: This report describes the dissociation of intra- and extra-hepatic immune responses during acute HEV infection. As shedding of the virus became solely intrahepatic, an immune profile reflective of the activity of hepatic resident cells was observed.